Question
The cost of 24 pens and 13 pencils is 175. What is the cost of 48 pens and 26 pencils?
24 पेन और 13 पेंसिल की लागत 175 है। 48 पेन और 26 पेंसिल की कीमत क्या है?
A.
B.
C.
D.
Answer
D.The cost of 24 pens and 13 pencils is 175. 24 pens+ 13 pencils=175 Multiply it by 2 48 pens + 26 pencils=350 So the correct answer is option D.
D.24 पेन और 13 पेंसिल की लागत 175 है। 24 पेन + 13 पेंसिल = 175 इसे 2 से गुणा करने पर 48 पेन + 26 पेंसिल = 350 इसलिए सही उत्तर विकल्प D है।

View Similar questions (संबन्धित प्रश्न देखें)

Question
175 - 25 ÷ 5 + 2 x 3 + 10 = ?
175 - 25 ÷ 5 + 2 x 3 + 10 =?
A.
B.
C.
D.
Answer
A.175 - 25 ÷ 5 + 2 x 3 + 10 From the rule of BODMAS 175 - 5+6+10=186 So the correct answer is option A.
A.175 - 25 ÷ 5 + 2 x 3 + 10 BODMAS के नियम से 175 - 5 + 6 + 10 = 186 इसलिए सही उत्तर विकल्प A है।
Question
If a-b=1 and a^3-b^3 = 61, then the value of ab will be.
यदि a-b = 1 और a^3-b^3= 61 है, तो ab का मान होगा?
A.
B.
C.
D.
Answer
B.a-b=1 a^3-b^3= 61 (a-b)^3=a^3-b^3-3ab(a-b) (1)^2=61-3ab(1) 3ab=61-1 3ab=60 ab=60/3 ab=20 So the correct answer is option B.
B.a-b=1 a^3-b^3= 61 (a-b)^3=a^3-b^3-3ab(a-b) (1)^2=61-3ab(1) 3ab=61-1 3ab=60 ab=60/3 ab=20 इसलिए सही उत्तर विकल्प B है।
Question
If P = (v7 - v6)/(v7 + v6), then what is the value of P + (1/P)?
यदि P = (√7 - √6)/(√7 + √6), तो P + (1/P) का मान क्या है?
A.
B.
C.
D.
Answer
D.P = (√7 - √6)/(√7 + √6) = P + (1/P) = (√7 - √6)/(√7 + √6) +[1/(√7 - √6)/(√7 + √6) ] =(√7 - √6)/(√7 + √6) +(√7 + √6)/(√7 - √6) =7+6-2√42 +7+6+2√42/7-6 =13+13 =26 So the correct answer is option D.
D.P = (√7 - √6)/(√7 + √6) = P + (1/P) = (√7 - √6)/(√7 + √6) +[1/(√7 - √6)/(√7 + √6) ] =(√7 - √6)/(√7 + √6) +(√7 + √6)/(√7 - √6) =7+6-2√42 +7+6+2√42/7-6 =13+13 =26 इसलिए सही उत्तर विकल्प D है।
Question
(a + b + c)² – (a – b – c)² = ?
(a + b + c)² - ((a - b - c)² =?
A.
B.
C.
D.
Answer
A.(a + b + c)² a²+b²+c²+2ab+2bc+2ca ( a - b - c )² =[ a+ ( - b ) + ( -c ) ]² =a²+(-b)²+(-c)²+2a(-b)+2(-b)(-c)+2(-c)a = a² + b² + c² - 2ab + 2bc - 2ca (a + b + c)²-( a - b - c )² a²+b²+c²+2ab+2bc+2ca - [a² + b² + c² - 2ab + 2bc - 2ca] =a²+b²+c²+2ab+2bc+2ca - a²-b²-c²+2ab-2bc+2ca =4ab+4ac =4a(b+c) So the correct answer is option A.
A.(a + b + c)² a²+b²+c²+2ab+2bc+2ca ( a - b - c )² =[ a+ ( - b ) + ( -c ) ]² =a²+(-b)²+(-c)²+2a(-b)+2(-b)(-c)+2(-c)a = a² + b² + c² - 2ab + 2bc - 2ca (a + b + c)²-( a - b - c )² a²+b²+c²+2ab+2bc+2ca - [a² + b² + c² - 2ab + 2bc - 2ca] =a²+b²+c²+2ab+2bc+2ca - a²-b²-c²+2ab-2bc+2ca =4ab+4ac =4a(b+c) इसलिए सही उत्तर विकल्प A है।